2013
DOI: 10.1039/c2ta00925k
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic assembly of a side chain liquid crystal polymer containing sulfoalkoxy groups for anhydrous proton conduction

Abstract: A side chain liquid crystal polymer containing pendant sulfonic acid groups has been synthesized by post-polymerization functionalization of a brominated mesogenic precursor. A macroscopic alignment was achieved by mechanical shearing of the liquid crystal polymer in the smectic phase. The uniaxial layered assembly exhibited anisotropic proton conductivities under anhydrous conditions and has potential applications in medium temperature fuel cells.Scheme 1 Synthesis of the mesogenic P2 containing sulfonic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…This material design approach has been very widely adopted and remains an area of considerable research activity; recent examples of hydrogen-bonded systems have included both main chain [11][12][13] and side chain liquid crystal polymers (SCLCPs), [14,15] and new discotic systems. [16][17][18] Hydrogen bonding also plays a key role in driving liquid crystalline behaviour in a diverse range of other materials including commercially important high-performance fibres, [19] protonic conductors [20,21] and liquid crystal sugars. [22][23][24][25] Supramolecular SCLCPs have attracted particular attention and these have been assembled not only using hydrogen bonding (see, for example, [7,26,27]), but also by utilising other types of non-covalent interactions such as ionic bonding [28] and quadrupolar interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This material design approach has been very widely adopted and remains an area of considerable research activity; recent examples of hydrogen-bonded systems have included both main chain [11][12][13] and side chain liquid crystal polymers (SCLCPs), [14,15] and new discotic systems. [16][17][18] Hydrogen bonding also plays a key role in driving liquid crystalline behaviour in a diverse range of other materials including commercially important high-performance fibres, [19] protonic conductors [20,21] and liquid crystal sugars. [22][23][24][25] Supramolecular SCLCPs have attracted particular attention and these have been assembled not only using hydrogen bonding (see, for example, [7,26,27]), but also by utilising other types of non-covalent interactions such as ionic bonding [28] and quadrupolar interactions.…”
Section: Introductionmentioning
confidence: 99%
“…POM observation suggested that P S45 preserved its original morphology when it was quenched using liquid nitrogen from the nematic phase. In contrast with the sample resulted from the smectic phase, the quenched nematic P S45 did not form uniformly patterned structures on a macroscopic scale even after shearing (Figure ).…”
Section: Resultsmentioning
confidence: 94%
“…4‐(6‐Bromohexoxy)−4′‐hydroxy biphenyl ( 1 ) and 4‐(6‐acryloyloxyhexyloxy)benzoyl chloride ( 2 ) were synthesized according to the procedures described previously . The brominated mesomorphic poly(methyl acrylate) ( P Br ) was prepared according to our previous report …”
Section: Methodsmentioning
confidence: 99%
“…Proton conduction has been achieved for smectic, columnar and cubic liquid crystals containing benzenesulfonic acid or sulfonate over 100 • C [8][9][10]. We succeeded in obtaining proton conductivity of 4.7 × 10 −3 S cm −1 at 200 • C in the layered side-chain liquid crystal polymers bearing sulfonic acids [11]. Styrenic comb polymers self-assembling into supramolecular structures with cylindrical imidazole-rich domains showed proton conductivity of 10 −3 S cm −1 at 200 • C [12].…”
Section: Introductionmentioning
confidence: 94%